The vision of teachers from Ceará on racism in public schools - Pereira, Patrícia Pimentel; Gomes, Rickardo Léo Ramos; Filho, Ivan de Oliveira Holanda; Cruz, Marcos Paulo Mesquita da (Seven Editora, 2023)
Racism is a problem present in Brazilian schools that is perpetuated by invisible and surreptitious mechanisms that seek to maintain prejudiced ideas even in a modern society where it should not exist. This suggests that racism is still a reality in Brazilian society, including in schools, and measures need to be taken to combat it and promote a culture of respect for diversity and equality. The research specifically addresses how these mechanisms can be combated. A qualitative approach was adopted for this research, connected with a quantitative approach, both inserted in an exploratory character. The general objective of the research is to analyze teacher perceptions related to racism in public state schools in Ceará. The research presents assumptions and perspectives regarding racism in public state schools in Ceará. One of the main results of the research is to highlight the urgency of addressing racism through pedagogical and effective actions that can reject and combat discriminatory practices against black students in the school environment. This implies that it is necessary to implement concrete measures to promote inclusion and equality of opportunities in schools, such as diversity policies and awareness and training programs for teachers and students. Additionally, it is important to adopt a critical stance towards discriminatory practices and combat the naturalization of racism in society in general. DOI:https://doi.org/10.56238/ptoketheeducati-017